Self-evaluation in patients treated for anorexia nervosa in Lublin province - Katarzyna Książek; Kinga Grabska-Kusiak; Agata Słowińska; Piotr Dreher; Sylwia Mojsym-Korybska; Anna Małgorzata Jurek (Journal of Education, Health and Sport, 2018)
Introduction. Self-esteem, or esteem, towards oneself has a tremendous impact on the various areas of human functioning. However, sometimes ICD-10 eating disorders with anorexia nervosa may adversely affect the perception of one's own body along with its self-evaluation. According to current medical knowledge, these disorders belong to serious mental disorders occurring mainly in young girls and women.